PELAYANAN PERIZINAN MELALUI SISTEM ONLINE SINGLE SUBMISSION RISK BASED APPROACH (OSS RBA) PADA DINAS PENANAMAN MODAL PELAYANAN TERPADU SATU PINTU DAN TENAGA KERJA KABUPATEN KUANTAN SINGINGI - Milta, Chyndi Berliana; ', Mayarni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The Online Single Submission Risk Based Approach (OSS RBA) is a program for administering risk-based business licenses which is a refinement of the previous OSS, namely OSS version 1.1 with the aim of simplifying and speeding up the business permit process based on Government Regulation Number 5 of 2021 concerning Implementation of Risk-Based Business Licensing. Purpose of this research is to find out and analyze licensing services through OSS RBA in DPMPTSPTK Kuantan Singingi Regency, as well as obstacles in its implementation. The theoretical concept used by researchers is the theory by Indrajit in Atthahara (2018), namely the elements of Support, Capacity and Value. This research is a qualitative descriptive study. With data analysis including data reduction, data presentation, and generate conclusions. The results in this study indicate that the implementation of OSS RBA has been achieved based on indicators according to Indrajit in Atthahara (2018). However, besides that, the DPMPTSPTK of Kuantan Singingi Regency continues to strive to realize and support the implementation of OSS RBA so that the community/business actors can feel the benefits in business licensing. Direct outreach to the community/business actors is still being carried out to improve community human resources, which have low understanding of, in particular, the OSS RBA in issuing business licenses. the inhibiting factor is the low level of community human resources for the OSS RBA program and inadequate supporting facilities. Keywords : Business Licensing, OSS RBA